Guidebook On Molecular Modeling In Drug Design. - N. Claude Cohen,ed (Academic Press, 2006)
Molecular modeling has assumed an important role in understanding the three-dimensional aspects of specificity in drug-receptor interactions at the molecular level. Well-established in pharmaceutical research, molecular modeling offers unprecedented opportunities for assisting medicinal chemists in the design of new therapeutic agents. Advances made in computer hardware and in theoretical medicinal chemistry have